2020
DOI: 10.1101/2020.03.04.20026005
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transmission and clinical characteristics of coronavirus disease 2019 in 104 outside-Wuhan patients, China

Abstract: BackgroundCases with coronavirus disease 2019 (COVID-19) emigrated from Wuhan escalated the risk of spreading in other cities. This report focused on the outside-Wuhan patients to assess the transmission and clinical characteristics of this illness. MethodsContact investigation was conducted on each patient who admitted to the assigned hospitals in Hunan Province (geographically adjacent to Wuhan) from Jan 22, 2020 to Feb 12, 2020.Demographic, clinical, laboratory and radiological characteristics, medication t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 19 publications
(34 reference statements)
1
15
0
Order By: Relevance
“…Although SARS-CoV and SARS-CoV-2 both belong to the same genus betacoronavirus and cause severe upper respiratory illness in humans, their clinical presentation and immune responses are different from each other [3]. One of the unique features of this COVID-19 epidemic is the presence of many asymptomatic patients and the observation of significant viral shedding during incubation period [4,5]. Furthermore, serial viral load profile showed that the viral load of COVID-19 peaks around the time of symptom onset or at clinical presentation which is different from that of SARS or MERS when their viral load peak at about 7-10 days after symptom onset [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Although SARS-CoV and SARS-CoV-2 both belong to the same genus betacoronavirus and cause severe upper respiratory illness in humans, their clinical presentation and immune responses are different from each other [3]. One of the unique features of this COVID-19 epidemic is the presence of many asymptomatic patients and the observation of significant viral shedding during incubation period [4,5]. Furthermore, serial viral load profile showed that the viral load of COVID-19 peaks around the time of symptom onset or at clinical presentation which is different from that of SARS or MERS when their viral load peak at about 7-10 days after symptom onset [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The case number keepsincreasing. As of June 9, 2020, the global con rmed COVID-19 cases and deaths increased to 7039918 and 404396, respectively [2].Family clustering and hospital-based transmission were the two major epidemiological features of this outbreak at the early stage, and continued to be an important cause of community-based SARS-CoV-2 transmission in a low prevalence region [3][4][5][6][7][8].However, data concerning SARS-CoV-2 transmissibility in the incubation period and the diversity in disease progression among affected family members are very limited.…”
Section: Introductionmentioning
confidence: 99%
“…As of June 9, 2020, the global con rmed COVID-19 cases and deaths increased to 7039918 and 404396, respectively [2]. Family clustering and hospital-based transmission were the two major epidemiological features of this outbreak at the early stage, and continued to be an important cause of community-based SARS-CoV-2 transmission in a low prevalence region [3][4][5][6][7][8]. However, data concerning SARS-CoV-2 transmissibility in the incubation period and the diversity in disease progression among affected family members are very limited.…”
Section: Introductionmentioning
confidence: 99%